REFERENTS AND OBJECTS: A PARALLEL BETWEEN GENERAL SEMANTICS AND YOGĀCARĀ BUDDHISM. - Rowe, Thomas A. (ETC: A Review of General Semantics)
The article examines few parallels have been identified at multiple levels between the work of Alfred Korzybski and the Buddhist philosophical tradition starting with the teachings of the Buddha. It mentions that Korzybski and the Buddha both identified problematic thinking and a set of practices to solve the problem. In the 20th century, Korzybski described the disconnect between how we intentionally engage with objects and what is extensionally real.